2018
DOI: 10.1021/acsomega.8b00060
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Epimerization of Azlactone Rings: Keto–Enol Tautomerism or Base-Mediated Racemization?

Abstract: Azlactones are versatile heterocycles employed in a diversity of transformations; the main drawback of these cycles consists in the epimerization of the α-carbonyl stereocenter during its preparation. We hereby present a theoretical study to explain how the racemization occurs. Two hypotheses were investigated: the keto–enol tautomerism and the base-mediated racemization, through an enolate intermediate. The results showed that the latter is consistent with the experimental data and can spontaneously occur at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…[23] This investigation proposed that instead of the commonly suggested intramolecular ketoenol tautomerism, azlactone epimerization process proceeds though enolate formation, in which a base (such as EDC urea formed during azlactone formation) plays a key role (Scheme 5). [23] This investigation proposed that instead of the commonly suggested intramolecular ketoenol tautomerism, azlactone epimerization process proceeds though enolate formation, in which a base (such as EDC urea formed during azlactone formation) plays a key role (Scheme 5).…”
Section: Dynamic Kinetic Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] This investigation proposed that instead of the commonly suggested intramolecular ketoenol tautomerism, azlactone epimerization process proceeds though enolate formation, in which a base (such as EDC urea formed during azlactone formation) plays a key role (Scheme 5). [23] This investigation proposed that instead of the commonly suggested intramolecular ketoenol tautomerism, azlactone epimerization process proceeds though enolate formation, in which a base (such as EDC urea formed during azlactone formation) plays a key role (Scheme 5).…”
Section: Dynamic Kinetic Resolutionmentioning
confidence: 99%
“…Last year, our research group presented a DFT study concerning the epimerization of the α‐carbonyl stereocenter of oxazolones, which consists of a key pre‐requisite (enantiomeric interconversion) for the DKR process . This investigation proposed that instead of the commonly suggested intramolecular keto‐enol tautomerism, azlactone epimerization process proceeds though enolate formation, in which a base (such as EDC urea formed during azlactone formation) plays a key role (Scheme ).…”
Section: Ring‐opening Reactionsmentioning
confidence: 99%
“…In addition, the saturated azlactones are widely used as intermediates in the synthesis of different heterocyclic scaffolds (including, 1,3-oxazoles, pyrroles, pyrrolines, imidazoles, and imidazolines) or of acyclic derivatives with potential biological properties [ 25 , 26 ]. Thus, due to their synthetic and biological importance, several methods of preparing 1,3-oxazol-5(4 H )-ones have been developed, the most widely used being the intramolecular cyclization of N -acyl-α-amino acids mediated by a carboxylic group activator, including acetic anhydride, N , N ′-dicyclohexylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, chloromethylenedimethylammonium chloride (Vilsmeier reagent), and alkyl chloroformates in the presence of N -methylmorpholine [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], etc. Fujita and Kunishima used a one-pot synthesis of 1,3-oxazol-5(4 H )-ones by the N -acylation of α-amino acids with carboxylic acids and the subsequent cyclodehydration of the resulting N -acyl-α-amino acids by the addition of N , N -diethylaniline.…”
Section: Introductionmentioning
confidence: 99%
“…A further mechanism for keto‐enol tautomerizations is available, involving concerted movement of two protons between the substrate and an acid catalyst molecule, such as formic acid. Further studies have shown that acid catalyzed double hydrogen atom transfer reactions occur in a wide variety of situations, including other tautomerizations, decomposition and bimolecular reactions, and in keto‐enol tautomerizations of dimer complexes . Furthermore, this mechanism may also play a role in the isomerization of free radicals, in the hydration of SO 3 , and in the hydrolysis of carbonyl compounds in the atmosphere, as well as in the unimolecular rearrangement of oxygenated volatile organic compounds …”
Section: Introductionmentioning
confidence: 99%